Caspase-8 Deficient Osteoblastic Cells Display Alterations in Non-Apoptotic Pathways - Vesela, Barbora; Killinger, Michael; Rihova, Kamila; Benes, Petr; Svandová, Eva; Kratochvilová, Adela; Trcka, Filip; Kleparnik, Karel; Matalova, Eva (Frontiers in Cell and Developmental Biology, 2022)
Caspase-8 is the key component of the receptor-mediated (extrinsic) apoptotic pathway. Immunological localization of active caspase-8 showed its presence in osteoblasts, including non-apoptotic ones. Further in vivo exploration of caspase-8 functions in the bone is hindered by the fact that the caspase-8 knock-out is lethal prenatally. Examinations were thus performed using individual cell populations in vitro. In this study, caspase-8 was eliminated by the CRISPR/cas9 technology in MC3T3-E1 cells, the most common in vitro model of osteoblastic populations. The aim of the work was to specify the consequences of caspase-8 deficiency on non-apoptotic pathways. The impact on the osteogenic gene expression of the osteoblastic cells along with alterations in proliferation, caspase cascades and rapamycin induced autophagy response were evaluated. Osteogenic differentiation of caspase-8 deficient cells was inhibited as these cells displayed a decreased level of mineralization and lower activity of alkaline phosphatase. Among affected osteogenic genes, based on the PCR Array, major changes were observed for Ctsk, as down-regulated, and Gdf10, as up-regulated. Other significantly down-regulated genes included those coding osteocalcin, bone morphogenetic proteins (-3, -4 and -7), collagens (-1a1, -14a1) or Phex. The formation of autophagosomes was not altered in rapamycin-treated caspase-8 deficient cells, but expression of some autophagy-related genes, including Tnfsf10, Cxcr4, Dapk1 and Igf1, was significantly downregulated. These data provide new insight into the effects of caspase-8 on non-apoptotic osteogenic pathways.